Metal complexes as a promising source for new antibiotics - Frei, Angelo; Zuegg, Johannes; Elliott, Alysha G; Baker, Murray; Braese, Stefan; Brown, Christopher; Chen, Feng; Dowson, Christopher; Dujardin, Gilles; Jung, Nicole; King, A. Paden; Mansour, Ahmed M; et al. (Chemical science (Cambridge), 2020)
There is a dire need for new antimicrobial compounds to combat the growing threat of widespread antibiotic resistance. With a currently very scarce drug pipeline, consisting mostly of derivatives of known antibiotics, new classes of antibiotics are urgently required. Metal complexes are currently in clinical development for the treatment of cancer, malaria and neurodegenerative diseases. However, only little attention has been paid to their application as potential antimicrobial compounds. We report the evaluation of 906 metal-containing compounds that have been screened by the Community for Open Antimicrobial Drug Discovery (CO-ADD) for antimicrobial activity. Metal-bearing compounds display a significantly higher hit-rate (9.9%) when compared to the purely organic molecules (0.87%) in the CO-ADD database. Out of 906 compounds, 88 show activity against at least one of the tested strains, including fungi, while not displaying any cytotoxicity against mammalian cell lines or haemolytic properties. Herein, we highlight the structures of the 30 compounds with activity against Gram-positive and/or Gram-negative bacteria containing Mn, Co, Zn, Ru, Ag, Eu, Ir and Pt, with activities down to the nanomolar range against methicillin resistant S. aureus (MRSA). 23 of these complexes have not been reported for their antimicrobial properties before. This work reveals the vast diversity that metal-containing compounds can bring to antimicrobial research. It is important to raise awareness of these types of compounds for the design of truly novel antibiotics with potential for combatting antimicrobial resistance. There is a dire need for new compounds to combat antibiotic resistance: metal complexes might provide the solution. 906 metal complexes were evaluated against dangerous ESKAPE pathogens and found to have a higher hit-rate than organic molecules.